2018
DOI: 10.1111/gcb.14105
|View full text |Cite
|
Sign up to set email alerts
|

Carbon quality and soil microbial property control the latitudinal pattern in temperature sensitivity of soil microbial respiration across Chinese forest ecosystems

Abstract: Understanding the temperature sensitivity (Q ) of soil organic C (SOC) decomposition is critical to quantifying the climate-carbon cycle feedback and predicting the response of ecosystems to climate change. However, the driving factors of the spatial variation in Q at a continental scale are fully unidentified. In this study, we conducted a novel incubation experiment with periodically varying temperature based on the mean annual temperature of the soil origin sites. A total of 140 soil samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
93
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 48 publications
14
93
3
Order By: Relevance
“…Many factors, such as precipitation, vegetation type, soil properties or human activities, exert effects on SOC decomposition. (b) Many studies have used laboratory incubations (Lefèver et al, ; Plante et al, ; Wang, Liu, & Tian, ) and maintained a controlled environment to characterize and compare C and nutrient fluxes in soils isolated from plants. However, the lack of continuous C inputs from vegetation reduces the reliability of extrapolating such results to natural ecosystems (Gu, Post, & King, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors, such as precipitation, vegetation type, soil properties or human activities, exert effects on SOC decomposition. (b) Many studies have used laboratory incubations (Lefèver et al, ; Plante et al, ; Wang, Liu, & Tian, ) and maintained a controlled environment to characterize and compare C and nutrient fluxes in soils isolated from plants. However, the lack of continuous C inputs from vegetation reduces the reliability of extrapolating such results to natural ecosystems (Gu, Post, & King, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the Q 10 of SOC decomposition has gained increasing attention under the scenario of global warming because of its importance in regulating soil C cycling and potential response of SOC decomposition to climate change (e.g., Conant et al, ; Karhu et al, ; Wang et al, ). Numerous studies have attempted in exploring Q 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Results from previous studies demonstrated that Q 10 values had a high variation. This variation was related to not only incubation and calculation methods (Hamdi, Moyano, Sall, Bernoux, & Chevallier, ; Lin, Zhu, & Cheng, ), but also soil property such as soil C quality (Hartley & Ineson, ; Wang et al, ), C:N ratio (Haddix et al, ), pH (Craine, Fierer, & McLauchlan, ) and microbes (Karhu et al, ; Thiessen, Gleixner, Wutzler, & Reichstein, ). These studies have advanced our understanding of Q 10 and its potential controlling factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations